Investigation of Wall Effect Simulation Methods in Saline Density Currents - Somayyeh Mohammadiyan Lanbaran; Afshin Eghbalzadeh (مدل‌سازی پیشرفته در مهندسی عمران)
Density currents induced by salinity gradients, which arise from differences in dissolved material concentrations between two fluid bodies, are of significant importance in estuarine environments, lakes, and dam reservoirs. This study numerically investigates such flows using Fluent software. Initially, a comparison was conducted to ensure that the results obtained from the numerical simulation were in good agreement with laboratory observations. Subsequently, the effects of near-wall modeling approaches, including standard and non-equilibrium wall functions, as well as the enhanced near wall treatment, on flow simulation accuracy were evaluated. The results demonstrated that all three methods were reasonably capable of simulating the velocity and density distributions; however, their performance varied across different sections and regions of the flow. The standard wall function approach yielded higher accuracy in regions adjacent to the wall, whereas the enhanced near wall treatment approach produced more accurate results at the interface between the density current and the ambient fluid. Regarding the density distribution, although no major discrepancies were observed among the different methods, the enhanced near wall treatment approach provided slightly better results compared to the other two. Overall, based on the obtained results, it can be recommended that when using coarser computational grids, the standard wall function approach is more appropriate. This recommendation is supported by the ability to position the first grid point at a dimensionless wall distance "y" ^"+" of approximately 11.225, eliminating the need for highly refined meshing near the wall. However, when finer grids are employed, the use of a modified near-wall treatment approach may be more suitable. This is because it requires placing the first computational node very close to the wall, such that the "y" ^"+" value is around 1, which allows for a more accurate resolution of the near-wall flow behavior.